1988
DOI: 10.1063/1.99110
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of interface defects in mismatched epilayers by a reduction in growth area

Abstract: We have eliminated interface defects from the mismatched Ino.()S GaO 95 As/ (001) GaAs interface by controlling the size of the growth area. 2-Jim-high pillars with different lateral shapes and dimensions were defined within the GaAs substrate before the molecular beam epitaxial growth of 3500 A of In o. 05 Gao,!" As, greater than four times the critical thickness. On the pillars, the linear density of misfit dislocations was reduced from > 5000 dislocations!cm for large (several hundred pm lateral dimensions)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The linear density of the MDs along the ͓110͔ direction is larger than that of the MDs along the ͓110͔ direction. [12][13][14] Since the XRT image was recorded using an InP substrate reflection, we found that the MDs locate at the MQW substrate interface. The X-Y line in Fig.…”
Section: A Origin Of Dark Lines In -Pl Imagesmentioning
confidence: 99%
“…The linear density of the MDs along the ͓110͔ direction is larger than that of the MDs along the ͓110͔ direction. [12][13][14] Since the XRT image was recorded using an InP substrate reflection, we found that the MDs locate at the MQW substrate interface. The X-Y line in Fig.…”
Section: A Origin Of Dark Lines In -Pl Imagesmentioning
confidence: 99%
“…The origin of this disparity possibly come from the fact that dislocations in GaAs, a zincblende crystal, are orientation-dependent. They can be As-or Ga-terminated (α-or β-type) and have different velocities [13]. The greater average step height along the [110] direction results in the stronger contrast of [1][2][3][4][5][6][7][8][9][10] stripes seen in the AFM image of Fig.…”
mentioning
confidence: 97%
“…Thus, when the more sensitive large-area techniques of photoluminescence, cathodoluminescence, and electron-beam-induced current began to be used systematically critical thicknesses moved down to be more consistent with the equilibrium model (25) Secondly, it was shown that the number of dislocation sources in a given area of sample could be controlled by varying the area of the grown heterolayer (26). That is, by using mesaetching prior to growth the dislocation densities on GaInAsGaAs mesa interfaces dropped to zero for 67 prn diameter mesas.…”
Section: Strain and Misfit Dislocationsmentioning
confidence: 98%